2013
DOI: 10.1007/s10661-013-3510-y
|View full text |Cite
|
Sign up to set email alerts
|

Metals in sediments and mangrove oysters (Crassostrea rhizophorae) from the Caroni Swamp, Trinidad

Abstract: Metals can have significant impacts on inhabitants of mangrove swamps as well as consumers of mangrove-associated fauna. Yet, for several Caribbean islands, assessments regarding the impact of metals on such ecosystems are particularly sparse. The present study investigated the distribution and potential impact of Cd, Cr, Cu, Ni, Pb and Zn in the Caroni Swamp, Trinidad and Tobago's largest mangrove ecosystem. Surface sediments and mangrove oysters (Crassostrea rhizophorae) from 10 sites in the swamp were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Several anthropogenic sources, however, such as agriculture, aquaculture, and mining increase metal burdens exceeding natural levels. Since bivalves accumulate and exhibit efficient strategies to deal with the potential toxic effect of metals (Arifin & Bendell-Young, 1997), they are used as biomarkers for monitoring metal contamination in aquatic systems (Kanthai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several anthropogenic sources, however, such as agriculture, aquaculture, and mining increase metal burdens exceeding natural levels. Since bivalves accumulate and exhibit efficient strategies to deal with the potential toxic effect of metals (Arifin & Bendell-Young, 1997), they are used as biomarkers for monitoring metal contamination in aquatic systems (Kanthai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The literature emphasizes the abiotic importance through local hydrodynamics, the chemical form of pollutants, the presence of other substrates competing for binding sites, and the physicochemical composition of the adjacent medium 27,61,62 , whereas the biotic ones include the life-cycle stage, gender, specific genetics, and physiological conditions [63][64][65][66] . In this study, we found that the variations appear predominantly as a combined effect of the biomonitors' proximity to the source of pollution, seasonal and hydrodynamic variation, and prior exposure of the biomonitor to metal-contaminated environments.…”
Section: Resultsmentioning
confidence: 99%
“…The gently sloping foothills of the northern and central ranges and the nonflood prone areas of the Caroni floodplain are used extensively for built development, both industrial and residential. At present, there are also a number of agricultural ventures that exist in the area (Kanhai, Gobin, Beckles, Lauckner, & Mohammed, 2013). These ventures contribute to the chemical contamination of the Caroni Swamp through runoff into the rivers.…”
mentioning
confidence: 99%
“…Common land-based sources may include surface runoff from roadways as well as riverine inputs, while marinebased sources may include discharges from maritime vessels operating in adjacent waters as well as tidal deposition of mainland contaminants. In addition, it must be highlighted that the operation of boats (for ecotourism and fish/shellfish harvesting) within the boundaries of the swamp may also contribute to chemical contamination in the swamp (Siung-Chang, Norman, & Dalipsingh, 1987;Kanhai et al, 2013). The Caroni Swamp is therefore susceptible to different sources of pollution, both land-based and marine-based, and from within its boundaries (Kanhai et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation